2017
DOI: 10.1515/johh-2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stemflow on redistributing precipitation and infiltration around shrubs

Abstract: Abstract:The experiments of stemflow of two semiarid shrubs (Caragana korshinskii and Hippophae rhamnoides) and its effect on soil water enhancement were conducted from 1 st May to 30 th September of 2009-2013 in the Chinese Loess Plateau. Stemflow values in C. korshinskii and H. rhamnoides averaged 6.7% and 2.4% of total rainfall. The rainfall threshold for stemflow generation was 0.5 and 2.5 mm for C. korshinskii and H. rhamnoides. When rainfall was less than 17.0 mm, the funnelling ratios were highly variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…This is because the soil is getting saturated, thereby reducing its ability to absorb water. Jian et al (2018) also showed a similar pattern of logarithmic relationship (function) between the depth of infiltration and the amount of rain in the soil around shrub with an R 2 value 0.77 and 0.89 in positions around the shrub stems and an R 2 of 0.81 in the soil outside the shrub. From Figure 4 we can observe that in tillage with hoeing plus loosening (T2), a volume of 350 L of rain (equivalent to a rain thickness of 9.7 mm) can produce water infiltration up to a rooting depth of 20 cm.…”
Section: Infiltration Ratesupporting
confidence: 54%
See 1 more Smart Citation
“…This is because the soil is getting saturated, thereby reducing its ability to absorb water. Jian et al (2018) also showed a similar pattern of logarithmic relationship (function) between the depth of infiltration and the amount of rain in the soil around shrub with an R 2 value 0.77 and 0.89 in positions around the shrub stems and an R 2 of 0.81 in the soil outside the shrub. From Figure 4 we can observe that in tillage with hoeing plus loosening (T2), a volume of 350 L of rain (equivalent to a rain thickness of 9.7 mm) can produce water infiltration up to a rooting depth of 20 cm.…”
Section: Infiltration Ratesupporting
confidence: 54%
“…A very close relationship between rainfall duration and infiltration depth is shown by the high R2 value of all land preparation methods (R2 = 95% to 99%). Jian et al (2018) also found a positive relationship between the depth of infiltration and the amount of rain in the form of a logarithmic function.…”
Section: Water Infiltrationmentioning
confidence: 75%
“…First, there is a larger number of plant roots acting as preferential infiltration routes; second, fine-grained plant patches are more efficient in reducing runoff than the coarse-grained ones (Bautista et al, 2007). In addition, soil porosity is larger under plants (Mora and Lázaro, 2014), and plants further increase infiltration by intercepting rainfall and producing stemflow (Jian et al, 2018). Furthermore, under alpha grass, biocrust rarely develops (Eldridge et al, 2010), but under plants such as Euzomodendron bourgaeanum, Helianthemum almeriense or Salsola genistoides, which are in the Lepra plots, biocrust (which favours runoff) is much more frequent than the 20% of cases that Kidron (2015) found under the canopy at Nizana (Israel).…”
Section: Runoff On Biocrusts At the El Cautivo Field Sitementioning
confidence: 99%
“…Especially dry soils can cause water repellence or lead to shrinking, thus enhancing preferential flow (Beven & Germann, 2013; Jarvis, 2007; Nimmo, 2021). Compared to the spatial variation of net precipitation, research on the role of canopy processes on soil hydrology is much rarer and has mostly been performed in forests and shrublands (e.g., Bouten et al, 1992; Jian et al, 2018; Li et al, 2009; Metzger et al, 2017; Molina et al, 2019), while small structured vegetation communities are underrepresented (Dunkerley, 2000; Llorens & Domingo, 2007; Sadeghi et al, 2020). In forest ecosystems, it was investigated partly by using model‐based approaches and field observations on how canopy‐modified net precipitation patterns influence soil water content or soil water fluxes (Coenders‐Gerrits et al, 2013; Guswa, 2012; Klos et al, 2014; Metzger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%